1985
DOI: 10.1152/jappl.1985.58.3.717
|View full text |Cite
|
Sign up to set email alerts
|

Acute inhalation of cigarette smoke augments hypoxic chemosensitivity in humans

Abstract: Hypoxic and hypercapnic ventilatory responses were measured after two levels of acute inhalation of cigarette smoke, minimum-level nicotine smoke (smoke 1) and nicotine-containing smoke (smoke 2), in 10 normal men. Chemosensitivity to hypoxia and hypercapnia was assessed both in terms of slope factors for ventilation-alveolar PO2 curve (A) and ventilation-alveolar PCO2 line (S) and of absolute levels of minute ventilation (VE) at hypoxia or hypercapnia. Ventilatory response to hypoxia and absolute level of VE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…3,8-10 Among all the risk factors evaluated, habitual snoring has been shown in this and other studies [11][12][13] to correlate best with apneic activity during sleep. 3 While it is possible that tobacco-induced inflammatory changes in the upper airway could predispose to upper airway obstruction and disordered breathing during sleep, the observation that tobacco increases sensitivity of chemoreceptors to hypoxia 4,5 suggests that smoking could also protect against central apneas. 8,14 Snoring reflects a partial upper airway obstruction whereas during apnea the obstruction in the pharynx is usually total.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,8-10 Among all the risk factors evaluated, habitual snoring has been shown in this and other studies [11][12][13] to correlate best with apneic activity during sleep. 3 While it is possible that tobacco-induced inflammatory changes in the upper airway could predispose to upper airway obstruction and disordered breathing during sleep, the observation that tobacco increases sensitivity of chemoreceptors to hypoxia 4,5 suggests that smoking could also protect against central apneas. 8,14 Snoring reflects a partial upper airway obstruction whereas during apnea the obstruction in the pharynx is usually total.…”
Section: Discussionmentioning
confidence: 99%
“…These include a significant decrease in tidal volume and minute ventilation (hypopnea), respiratory pauses (apneas), and periodic breathing. [3][4][5] The objective of this study was to evaluate the influence of cigarette smoking behavior on the respiratory alterations occurring during sleep in a healthy population. 2 However, the existence of a relationship between cigarette smoking behavior and apneic activity during sleep is disputed.…”
mentioning
confidence: 99%
“…The CO 2 chemosensitivity values in healthy subjects were somewhat lower than previously reported by other studies but were similar to the value reported by Yamamoto and colleagues. 37 Chemosensitivity is known to be lower in the elderly than in the younger subjects 38 and chemosensitivity varies considerably between individual subjects, which may have affected our results.…”
Section: Effects Of Exercise Trainingmentioning
confidence: 93%
“…Several studies have documented altered levels of neurotransmitters (Hedner et al, 1980; Kaneko et al, 1985; Yamamoto et al, 1985; Yamamoto and Kato, 1986; Hadjiconstantinou et al, 1990; Seidler and Slotkin, 1990; Dell’Anna et al, 1993; Tanaka et al, 1995; Anju et al, 2010a,b; Anju and Paulose, 2011, 2013). However, there is little consensus over the direction or magnitude of changes (Decker M.J. et al, 2003; Decker et al, 2005).…”
Section: Evaluation Of Available Animal Models Of Neonatal Hypoxia Ismentioning
confidence: 99%